Forecast of Rice Reserves in Special Region of Yogyakarta - Candarisma Dhanes Noor Viana; Eka Nur Jannah; Hanna Syahrina Arumndalu (Jurnal Dinamika Sosial Ekonomi, 2022)
Food is one of the basic human needs. A priority food commodity is rice. The Special Region of Yogyakarta Province is one of the areas that has agricultural land that is able to supply the food needs in the area. However, the population in the Special Region of Yogyakarta is growing annually, having an impact on the food needs that have to be met. The study aimed to determine the food reserves, especially rice reserves, in the Special Region of Yogyakarta. This study used a descriptive analytical method and ARIMA forecasting model. The study used time series data from 2011 to 2021 obtained from the dataku application managed by BAPPEDA of the Special Region of Yogyakarta. The data consisted of rice production data, per capita consumption data, and population data. The results showed that the rice reserves in the Special Region of Yogyakarta from 2011 to 2021 decreased over years. Based on the forecasting results, the best model was ARIMA c(9,1,6). In addition, the result of the rice reserve forecast from 2022 to 2025 also showed a decreasing trend from year to year. Therefore, it is crucial for the government to make efforts to maintain food availability to achieve local food security.Keywords: ARIMA, Food Reserves Rice, Forecasting, Special Region of Yogyakarta